The pursuit of energy in refugee contexts: Discrimination, displacement, and humanitarian energy access for the Rohingya refugees displaced to Bangladesh. (January 2022) - Rafa, Nazifa; To, Thi Tuong Van; Gupta, Mukesh; Uddin, Sayed Mohammad Nazim
Abstract: Decades of discrimination under the Burmese government and the military's campaign of ethnic cleansing drove over 671, 000 Rohingyas out of Rakhine and into Bangladesh, where they were settled in make-shift camps. The provision of energy is often overlooked in refugee settlements, where energy facilities are underfunded, inefficient, or unsafe. This paper aims to serve as a scoping review and explores the energy-based needs and provision in the Rohingya refugee camps by drawing from examples and case studies conducted in refugee settlements worldwide. Common to several refugee settlements, Rohingyas rely on unsustainable energy sources like firewood to meet their household energy needs, resulting in numerous social, health, and environmental risks. Initiatives have been undertaken to address their energy needs, such as the distribution of LPG stoves and fuel, and the installation of biogas digesters and solar-powered homes, health centers, and water systems. However, such projects are underfunded or applied on a short scale. This paper calls for further research on the characterization and scale of energy requirements of the Rohingya refugees as well as the formulation of national policies that consider the synergies between energy poverty and socioeconomic, environmental, and political dimensions. Energy access must be viewed as more than just a technological issue. It must be placed as a part of a larger discourse and means for addressing issues in humanitarian crises, in collaboration with the communities concerned. In addition, it also promotes the exploration of the use of hybrid energy systems in the camps to address their energy needs.